ANALISIS FAKTOR â FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wisnu Aditya Irzaputra, 12.05.52.0064; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
This study aims to determine the effect of Leverage, Profitability, Liquidity, Size And rowth of the Dividend Policy on manufacturing companies in Indonesia Stock Exchange (BEI).Â The population is all manufacturing companies in the Indonesia Stock Exchange (BEI) by the number of 460 companies and research over the period 2011 to 2013. The sample in this research is 108 companies. The sampling technique used was purposive sampling. The analytical tool used in this research is Multiple Regression Analysis.Â The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 51.8%. As for the statistical tests F-test shows that, between leverage, profitability, liquidity, size and investment jointly affect the dividend policy. And partial hypothesis testing results show that there are positive influence between leverage, profitability, liquidity and size of the dividend policy. As for the investment shows there is a negative effect on dividend policy.Keywords: Leverage, Profitability, Liquidity, Size, Growth, Dividend Policy